Myasis in uterine prolapse - Siu Au, Alejandro (2015)
We report a case of a 95 year-old woman, from Oxapampa, Peru, with fourth degree prolapsed uterus infested with dipterous larvae. Myiasis is an infestation of the human tissue produced by flies´ larvae, or maggots,which feed on the host´s living or dead tissue, liquid body substances or ingested food. This is a rare condition and there has been only two cases reported in the literature. Maggots were removed manually, instilled with a combination de Coumaphos 300 mg, Propoxur 20 mg and Prontalbin 50 mg dusting powder, a veterinarian product, and treated with broad spectrum antibiotic.